Canadian Association of Gastroenterology Clinical Practice Guidelines: The Use of Tumour Necrosis Factor-Alpha Antagonist Therapy in Crohn's Disease. (2009) - Sadowski, Daniel C; Bernstein, Charles N; Bitton, Alain; Croitoru, Ken; Fedorak, Richard N; Griffiths, Anne; the CAG Crohn's Consensus Group
Abstract : BACKGROUND: Guidelines regarding the use of infliximab in Crohn's disease were previously published by the Canadian Association of Gastroenterology in 2004. However, recent clinical findings and drug developments warrant a review and update of these guidelines. OBJECTIVE: To review and update Canadian guidelines regarding the use of tumour necrosis factor-alpha antibody therapy in both luminal and fistulizing Crohn's disease. METHODS: A consensus group of 25 voting participants developed a series of recommendation statements that addressed pertinent clinical questions and gaps in existing knowledge. An iterative voting and feedback process was used in advance of the consensus meeting in conjunction with a systematic literature review to refine the voting statements. These statements were brought to a formal consensus meeting held in Montreal, Quebec (March 2008), wherein each statement underwent discussion, reformulation, voting and subsequent revision until group consensus was obtained (at least 80% agreement). OUTCOME: The 47 voting statements addressed three themes: induction therapy, maintenance therapy and safety issues. As a result of the iterative process, 23 statements achieved consensus and were submitted for publication. CONCLUSION: In the past five years, tumour necrosis factor-alpha antagonist therapy has become a cornerstone in the management of moderate-to-severe Crohn's disease refractory to conventional treatment algorithms. The evidentiary base supporting the use of these drugs in Crohn's disease is substantial and strengthened by results from long-term clinical and molecular studies. However, significant gaps in knowledge exist, particularly with regard to treatment failure. Confidence in the safety of these drugs is increasing, provided that therapy is administered in a clinical setting in which potential complications can be readily recognized and treated.